2015
DOI: 10.1007/s00330-015-4060-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the image qualities of filtered back-projection, adaptive statistical iterative reconstruction, and model-based iterative reconstruction for CT venography at 80 kVp

Abstract: • MBIR provides superior image quality compared with FBP and ASIR • CTV at 80kVp with MBIR improves diagnostic confidence in diagnosing DVT • CTV at 80kVp with MBIR presents better image quality with low radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…[ 3 ] Many studies have proved that low tube voltage was a practical approach applied to reduce radiation dose during CT acquisition. [ 7 9 ] Nakaura et al [ 10 ] has also confirmed that the radiation dose decreased by 20% when the tube voltage decreased from 120 to 80 kVp. However, a principal byproduct of low tube voltage is the loss of image quality because of the associated increase in image noise and higher susceptibility to beam-hardening artifacts, especially for those patients with high body mass index (BMI).…”
Section: Introductionmentioning
confidence: 91%
“…[ 3 ] Many studies have proved that low tube voltage was a practical approach applied to reduce radiation dose during CT acquisition. [ 7 9 ] Nakaura et al [ 10 ] has also confirmed that the radiation dose decreased by 20% when the tube voltage decreased from 120 to 80 kVp. However, a principal byproduct of low tube voltage is the loss of image quality because of the associated increase in image noise and higher susceptibility to beam-hardening artifacts, especially for those patients with high body mass index (BMI).…”
Section: Introductionmentioning
confidence: 91%
“…SAFIRE, one of the recently introduced IR algorithms, has been shown to be helpful to reduce image noise and improve the image quality even in the low tube voltage setting at various clinical applications [ 19 , 33 39 ]. Although FBP has been widely used as the conventional CT image reconstruction algorithm for decades, its drawbacks are known to be relatively high levels of image noise and streaky artifacts, particularly when low dose CT acquisition is made [ 22 , 40 ]. In a recent study about 70 kVp CT angiography in children, Pei et al [ 36 ] have demonstrated that overall image quality including graininess, sharpness was significantly improved with SAFIRE, as well as a lower image noise and higher SNR and CNR were achieved with SAFIRE compared to FBP algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…For subjective analysis, two radiologists with 4 and 9 years of experience independently evaluated the randomized, axial CTV images, blinded to the scanning protocol. The readers recorded scores using a previously designed template for the following characteristics [ 11 , 22 ]; image quality (5, excellent, optimal enhancement to allow confident diagnosis of the presence or absence of a clot, superior to a score of 4; 4, good, optimal enhancement to allow confident diagnosis of the presence or absence of a clot; 3, equivocal, enhancement sufficient for diagnosis; 2, poor, inadequate for diagnosis of the presence or absence of a clot; 1, unacceptable, no diagnosis possible); image noise (1, optimal, none perceivable; 2, moderate, but sufficient for diagnosis; 3, unacceptable, no diagnosis possible) (Figs 1 and 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 , 16 , 17 ] Most previous studies on low kilovoltage CTV have demonstrated increased iodine contrast in the veins, but relatively few have evaluated this with regard to DVT. [ 7 , 8 , 10 , 13 16 ] Moreover, the majority have made comparisons between 120 and 100 kVp, [ 8 , 11 , 14 ] or 120 and 80 kVp. [ 13 , 15 ] Only Cho et al [ 11 ] compared contrast of thrombi to veins in the 100 and 120 kVp settings and demonstrated higher contrast at 100 kVp in the clinical human study.…”
Section: Introductionmentioning
confidence: 99%